2014
DOI: 10.1002/anie.201407362
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence, Stability, and Proton Response of an Open‐Shell (3,5‐Dichloro‐4‐pyridyl)bis(2,4,6‐trichlorophenyl)methyl Radical

Abstract: A luminescent open-shell organic radical with high chemical stability was synthesized. (3,5-Dichloro-4-pyridyl)bis(2,4,6-trichlorophenyl)methyl radical (PyBTM) was photoluminescent under various conditions. Fluorescence quantum yields of 0.03, 0.26, and 0.81 (the highest value reported for a stable organic radical) were obtained in chloroform, in poly(methyl methacrylate) film at room temperature, and in an EPA matrix (diethyl ether:isopentane:ethanol) at 77 K, respectively. The photostability of PyBTM is up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

22
286
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 207 publications
(308 citation statements)
references
References 15 publications
22
286
0
Order By: Relevance
“…TTM radical showed a clear reversible redox couple with the cathodic peak at approximately -0.8 V vs. Ag/AgCl, corresponding to the formation of TTM-anion, and the anodic peak at around -0.6 V vs. Ag/AgCl corresponding to the formation of TTM-radical (see Figure S2). CVs are well consistent with those published previously by Hattori et al 37 Before assembling the battery, TTM chemical stability with metallic lithium was also tested and no decomposition was observed (see Figure S3). Figure 1 depicts CVs of a common Super P electrode in O 2saturated electrolyte containing TEGDME and LiOTf (1M) with and without TTM-radical (1 mM), performed in a Teflon homemade Li-O 2 cell.…”
supporting
confidence: 89%
“…TTM radical showed a clear reversible redox couple with the cathodic peak at approximately -0.8 V vs. Ag/AgCl, corresponding to the formation of TTM-anion, and the anodic peak at around -0.6 V vs. Ag/AgCl corresponding to the formation of TTM-radical (see Figure S2). CVs are well consistent with those published previously by Hattori et al 37 Before assembling the battery, TTM chemical stability with metallic lithium was also tested and no decomposition was observed (see Figure S3). Figure 1 depicts CVs of a common Super P electrode in O 2saturated electrolyte containing TEGDME and LiOTf (1M) with and without TTM-radical (1 mM), performed in a Teflon homemade Li-O 2 cell.…”
supporting
confidence: 89%
“…The enhanced uorescence quantum yields of F 2 PyBTM were almost proportional to the decrease of non-radiative decay rate (k nr ) estimated from the uorescence lifetime (s) measurements and the equations f ¼ k f /(k f + k nr ) and s ¼ 1/(k f + k nr ); where k f indicates the radiative rate. 4 Photostability, an important property of luminescent radicals, was investigated by measuring the decay of uorescence intensity upon continuous photoirradiation (370 nm excitation wavelength) in dichloromethane. Because the van der Waals radius of an F atom is smaller than that of either Cl or Br, the pyridyl ring in F 2 PyBTM suffers less steric congestion, and can adopt a conformation more closely coplanar to the sp 2 plane of the central carbon (C4C10C16 plane; see Table S2, ESI †).…”
mentioning
confidence: 99%
“…This affords stronger p-conjugation between the two moieties. 4,10 As the electron-withdrawing nature of the halogen atom increases, the acidity of these acids increases. The enhanced p-conjugation suppresses the thermal uctuation and vibration of molecules that would cause non-radiative decay.…”
mentioning
confidence: 99%
“…[2][3][4][5][6] This modulation dynamically changes the distribution of spin states (i.e., spin statistics) in the excited state and the yield of luminescent recombined species,resulting in magnetic field-sensitive luminescent properties.M FEs have also been observed in other processes involving changes in the spin multiplicity in the excited state,such as triplet-triplet annihilation. [11] Recent developments in highly photostable luminescent radicals have revealed unique emission characteristics based on their doublet states,s uch as efficient electron-photon conversion in electroluminescent devices and the absence of the heavy metal effect. [11] Recent developments in highly photostable luminescent radicals have revealed unique emission characteristics based on their doublet states,s uch as efficient electron-photon conversion in electroluminescent devices and the absence of the heavy metal effect.…”
mentioning
confidence: 99%
“…[7][8][9][10] Stable organic radicals have long been considered as nonemissive or highly light-sensitive species. [11][12][13][14][15] An important challenge that remains in luminescent radicals research is to develop photofunctionalities based on the interplay between luminescence and spin, such as magnetoluminescence.T here are no reported examples of the apparent magnetoluminescence of stable radicals, and Li et al have shown the absence of MFE on electroluminescence for the fields of smaller than 200 mT at room temperature. [11][12][13][14][15] An important challenge that remains in luminescent radicals research is to develop photofunctionalities based on the interplay between luminescence and spin, such as magnetoluminescence.T here are no reported examples of the apparent magnetoluminescence of stable radicals, and Li et al have shown the absence of MFE on electroluminescence for the fields of smaller than 200 mT at room temperature.…”
mentioning
confidence: 99%